Determining the Prognosis of Bell's Palsy Based on Severity at Presentation and Electroneuronography. (30th March 2021) - Escalante, Derek A.; Malka, Ronit E.; Wilson, Allison G.; Nygren, Zachary S.; Radcliffe, Kristofer A.; Ruhl, Douglas S.; Vincent, Aurora G.; Hohman, Marc H.
Abstract : Objective: To examine the demographics of Bell's palsy and determine how House‐Brackmann (HB) grade at nadir and electroneuronography (ENoG) results correlate with HB grade after recovery and development of synkinesis. Study Design: Retrospective cohort study. Setting: Tertiary care military medical center. Methods: Patients with acute Bell's palsy and adequate follow‐up, defined as 6 months or return to HB grade I function, were included. Demographic information, HB scores at nadir and recovery, and ENoG results were collected. Results: A total of 112 patient records were analyzed. Ages ranged from 8 to 87 years with peaks at 21 to 25 and 61 to 65 years. Among patients, 16.3% reached a nadir at HB II, 41.9% at HB III, 5.4% at HB IV, 16.3% at HB V, and 20.1% at HB VI. The overall recovery rate was 73.2% to HB I function, 17.0% to HB II, and 9.8% to HB III. The chance of recovery to HB I decreased as the severity of paralysis increased ( rs = −1.0, P <. 0001). Mean time to recovery to HB I was 6 weeks. Greater degeneration on ENoG suggested worse recovery ( rs = 0.62, P =. 01). Patients with HB V and VI were most likely to develop synkinesis. Conclusion: More severe paralysis increased the chance of recovery to HB II or III function. The granularity of this study provides prognostic insights that may inform the counseling of patients with Bell's palsy with respect to prognosis and recovery timeline.